Extended UTAUT2-Based Analysis of User Acceptance of EIGER’s Mobile Shopping App - Perdananti, Primanola; Noviaristanti, Siska (Journal Research of Social Science, Economics, and Management, 2025)
This study investigates user acceptance of the EIGER Adventure mobile application, designed to enhance online shopping convenience for outdoor gear enthusiasts in Indonesia. The research employs an extended UTAUT2 model, incorporating Perceived Risk and Trust variables, to analyze factors influencing consumer behavior. A purposive sampling method was used to collect data from 478 respondents who are active users of the EIGER application. The research adopts a quantitative approach, with data analyzed using Structural Equation Modeling (SEM) through SmartPLS 4. The results indicate that Social Influence and Trust significantly affect Behavioral Intention to use the app, while Habit influences both Behavioral Intention and Use Behavior. Furthermore, Behavioral Intention was found to have a positive impact on Use Behavior, suggesting that users’ intention to use the app strongly predicts actual usage behavior. These findings offer valuable insights into the factors driving user acceptance and app adoption, emphasizing the importance of Trust and Social Influence in shaping consumer behavior. The study also highlights the role of Habit in both the intention to use and actual usage of mobile shopping apps. Based on these findings, the study provides recommendations for strategies to improve user engagement and optimize the development of mobile shopping apps, particularly in the outdoor gear industry, to better meet consumer expectations and enhance the overall shopping experience